Privacy and Security Implementation in Existing Cloud Based Electronic Health Records - A DetailedReview - S. Prathima,Dr.C. Priya (International Journal of Advanced Science and Technology, 2020)
Over the recent years, cloud computing has emerged as a powerful means for providing automated healthcare facilities. Cloud helps in massive sharing of information between doctors and hospitals using Electronic Health Records. This major transformation has changed the way doctors and hospitals deliver quality and effective service to their patients. Using Cloud storage inhealthcare services has revolutionized health industry, making it more efficient. Apart from the primary driving factors of cloud like flexibility in cost of maintenance, infrastructure and development, on-demand scalability of storage centers and pay on use schemes are proven to be most effective. More and more digitalization of data causes breech of security and privacy.Because healthcare information is a highly sensitive data which cannot be compromised,the future of healthcare relies in providing secure and trustworthy sharing of data by safeguarding privacy and trust. This paper gives an extensive review of the existing security mechanisms for Cloud based healthcare systems.